Description of life cycle and preimaginal stages of Alecton discoidalis Laporte, 1833 (Coleoptera: Lampyridae) under laboratory conditions - Madruga, Ormaily; Branham, Marc A. (Zootaxa, 2020)
Alecton discoidalis Laporte, 1833 is the most widespread species of the only firefly genus endemic to Cuba. It is commonly found in limestone landscapes across the western half of the country. Larvae of A. discoidalis were collected at Pan de Matanzas and reared through the adult stage under laboratory conditions. Larvae were fed mainly terrestrial snails from the families Potamiidae and Helicinidae. Alecton discoidalis underwent between four and eight larval instars. Females had more larval instars than males likely due to the need to gain more body mass for egg production. Eggs, larvae and pupae are described and illustrated, with emphasis on general body shape, as well as details of the larval head, antennae and mouthparts. Alecton discoidalis females are both brachypterous and physogastric.